"Physical activity is beneficial to anyone, including those with ASD": Antecedents of nurses recommending physical activity for people with autism spectrum disorder. (February 2021) - Tiner, Sarah; Cunningham, George B; Pittman, Alison
People with autism spectrum disorder are less physically active than are their peers. Nurses can play a key role in helping to promote such behaviors, but they do so sparingly. The purpose of this study, therefore, was to examine the degree to which nurses recommend physical activity to patients with autism spectrum disorder, and to identify antecedents thereof. Adopting a mixed methods approach, data were collected from a representative sample of nurses ( n = 180) working in the United States. Results from regression analyses indicate that nurses were only moderately likely to recommend physical activity. When perceived barriers to physical activity were low, perceived benefits of physical activity held a positive, significant association with recommendations. However, when perceived barriers were high, the relationship between perceived benefits and recommendations was no longer significant. Inductive thematic analysis of the qualitative data showed the value nurses place on physical activity, how they interpret barriers and benefits, and strategies for making physical activity inclusive for people with autism spectrum disorder. In conclusion, nurses have an opportunity to more frequently promote physical activity to their patients with autism spectrum disorder and, in doing so, help mitigate some of the poor health outcomes people with autism spectrum disorder experience. Lay abstract: Participation in regular physical activity is linked with physical, psychological, and social improvements. Nevertheless, persons with autism spectrum disorder participate at lower levels than do their peers. Nurses can play a key role in helping to promote such behaviors, but do so sparingly. The purpose of this study is to examine the degree to which nurses recommend physical activity to people with autism spectrum disorder. Even though a number of scholars have examined the role of health professionals in promoting physical activity, comparatively little research has examined nurses. Further, previous scholars have largely focused on the promotion of physical activity to patients in general. However, people with disabilities and people with autism spectrum disorder, specifically, are frequently overlooked when it comes to physical activity promotion. Data were collected from a representative sample of nurses ( n = 180) working in the United States. Results indicate that nurses were only moderately likely to recommend physical activity. When perceived barriers were low, perceived benefits held a positive, significant association with recommendations. However, when perceived barriers were high, the relationship between perceived benefits and recommendations was no longer significant. Analysis of qualitative data showed the value nurses place on physical activity, how they interpret barriers and benefits, and strategies for making physical activity inclusive for people with autism spectrum disorder. In conclusion, nurses have an opportunity to more frequently promote physical activity to their patients with autism spectrum disorder and, in doing so, help mitigate some of the poor health outcomes people with autism spectrum disorder experience. The authors identified implications for nursing education and professional development, as well as for sport and recreation managers charged with delivering physical activity to people with autism spectrum disorder.